2006
DOI: 10.1111/j.1472-8206.2006.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β‐adrenoceptor antagonists as substrates and inhibitors of the drug transporter P‐glycoprotein1

Abstract: Transporter proteins such as P-glycoprotein are major determinants of intracellular drug concentrations. Moreover, inhibition or induction of transporters is an important mechanism underlying drug interactions in humans. However, very little is known whether beta-adrenoceptor antagonists are substrates and/or inhibitors of P-glycoprotein. Therefore, we investigated the P-glycoprotein-mediated transport of propranolol, metoprolol, bisoprolol, carvedilol and sotalol in P-glycoprotein-expressing Caco-2 monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 43 publications
(48 reference statements)
4
52
0
2
Order By: Relevance
“…Additionally, CAR is able to reverse multidrug resistance to anticancer drugs through p-Gp inhibition. The major molecular targets of CAR include the membrane adrenoreceptors (ß-1, ß-2 and ·-1), growth factor receptors including platelet-derived growth factor receptors (PDGFr), reactive oxygen species, ion channels (K + and Ca 2+ ), p-Gp and mitochondria (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CAR is able to reverse multidrug resistance to anticancer drugs through p-Gp inhibition. The major molecular targets of CAR include the membrane adrenoreceptors (ß-1, ß-2 and ·-1), growth factor receptors including platelet-derived growth factor receptors (PDGFr), reactive oxygen species, ion channels (K + and Ca 2+ ), p-Gp and mitochondria (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Moriki et al (2005) have provided evidence that P-glycoprotein acts as BBB efflux transporter for this compound. However, DPHM is not a P-glycoprotein substrate (Chen et al, 2003), although we have previously shown that propranolol, which inhibits P-glycoprotein (Bachmakov et al, 2006), significantly increases the brain/plasma ratios of DPHM in adult sheep (Au-Yeung et al, 2006). The identity of CNS efflux transporter for DPHM remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the linezolid-omeprazole interaction could be particularly relevant among poor metabolizers of CYP2C19. However, it has also been found that for barnidipine and carvedilol the IC 50 s for inhibition of P-gp-mediated transport were even lower (8.6 M for barnidipine [7] and 0.16 M for carvedilol [2]) and in the range of their respective plasma concentrations. This suggests that linezolid overexposure could be particularly relevant among patients who receive cotreatment with all of these different P-gp inhibitors.…”
mentioning
confidence: 99%
“…It has been recently suggested that linezolid may be a substrate of P-glycoprotein (P-gp) and that significant overexposure may occur in the presence of some P-gp inhibitors, namely, omeprazole, amiodarone, and amlodipine (13). Interestingly, three of the drugs of the complex polytherapy of our patient, namely, omeprazole, barnidipine, and carvedilol, are potent P-gp inhibitors (2,8,12). Of note, the half-maximal inhibitory concentration (IC 50 ) of omeprazole against P-gp-mediated transport was found to be 17.7 M, which is higher than its expected plasma concentrations at therapeutic doses, but not if considering poor metabolizers of CYP2C19 (12).…”
mentioning
confidence: 99%